(untitled) (International Journal of Physiology, 2021)
Background: - Pre-eclampsia is a serious complication of pregnancy and contributes significantly maternal as well as perinatal morbidity and mortality. So this study is done to find if there exists any relationship between maternal age and pre-eclampsia. Aim:- To study what age group is more prone to development of pre-eclampsia in normal pregnancies. Methodology:- 400 pre-eclamptic women in age group 18-42 years were included in the study. Cases are divided according to different age group. Result:- Higher incidence of pre-eclampsia was observed in the age group 18-26 years followed by 35-42 years. Discussion:- Age is found to be related to pre-eclampsia. Conclusion:- From this study, this can be concluded that age less than 25 years and age greater than 35 years are more prone to development of pre-eclampsia.